2004
DOI: 10.1016/j.ymthe.2004.07.021
|View full text |Cite
|
Sign up to set email alerts
|

A Phase I Open-Label, Dose-Escalation, Multi-Institutional Trial of Injection with an E1B-Attenuated Adenovirus, ONYX-015, into the Peritumoral Region of Recurrent Malignant Gliomas, in the Adjuvant Setting

Abstract: ONYX-015 is an oncolytic virus untested as a treatment for malignant glioma. The NABTT CNS Consortium conducted a dose-escalation trial of intracerebral injections of ONYX-015. Cohorts of six patients at each dose level received doses of vector from 10(7) plaque-forming units (pfu) to 10(10) pfu into a total of 10 sites within the resected glioma cavity. Adverse events were identified on physical exams and testing of hematologic, renal, and liver functions. Efficacy data were obtained from serial MRI scans. No… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
248
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 391 publications
(256 citation statements)
references
References 27 publications
3
248
0
1
Order By: Relevance
“…However, these tumor cells may be eradicated by administration of viral vectors carrying suicide genes such as thymidine kinase (TK) or cytosine deaminase (CD). 2,3 Adenoviral vectors are among the most promising gene delivery vehicles currently available because: (1) intratumoral administration of adenovirus type 5 (Ad5)-based vectors in malignant glioma patients has demonstrated excellent safety; [4][5][6][7] (2) high titer batches of Ad5 can be produced at large scale; (3) large segments of foreign DNA can be incorporated into Ad5 and (4) Ad5 does not integrate into the host genome. In a recently published randomized controlled study, Ad5-TK increased the median survival time from 38 to 62 weeks in malignant glioma patients.…”
Section: Introductionmentioning
confidence: 99%
“…However, these tumor cells may be eradicated by administration of viral vectors carrying suicide genes such as thymidine kinase (TK) or cytosine deaminase (CD). 2,3 Adenoviral vectors are among the most promising gene delivery vehicles currently available because: (1) intratumoral administration of adenovirus type 5 (Ad5)-based vectors in malignant glioma patients has demonstrated excellent safety; [4][5][6][7] (2) high titer batches of Ad5 can be produced at large scale; (3) large segments of foreign DNA can be incorporated into Ad5 and (4) Ad5 does not integrate into the host genome. In a recently published randomized controlled study, Ad5-TK increased the median survival time from 38 to 62 weeks in malignant glioma patients.…”
Section: Introductionmentioning
confidence: 99%
“…First-generation adenoviral vectors are powerful vectors for gene transfer and gene therapy in the CNS (Bilang-Bleuel et al, 1997;Bemelmans et al, 1999;Dewey et al, 1999;Bjorklund et al, 2000;Mittoux et al, 2000;Sandmair et al, 2000;Maleniak et al, 2001;Mittoux et al, 2002;Biglari et al, 2004;Chiocca et al, 2004;Do Thi et al, 2004;Gondi et al, 2004;HurtadoLorenzo et al, 2004;Immonen et al, 2004). As a result, recent trials have shown adenoviral vectors encoding HSV1-TK to be effective in randomized clinical trials for brain glioblastoma multiforme, compared to patients treated with standard treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Experimentally, they are successful in gene therapy models of many brain diseases, including Parkinson's disease (Bilang-Bleuel et al, 1997;Bjorklund et al, 2000;Do Thi et al, 2004;), Huntington's disease (Bemelmans et al, 1999;Mittoux et al, 2000;Mittoux et al, 2002), brain tumors (Dewey et al, 1999;Sandmair et al, 2000;Maleniak et al, 2001;Biglari et al, 2004;Chiocca et al, 2004;Gondi et al, 2004;Immonen et al, 2004) and various pain syndromes (Cope et al, 2006). In comparative clinical trials of gene therapy for malignant brain tumors, first-generation adenoviral vectors are significantly more effective than retroviral vectors, utilizing the conditional cytotoxic gene HSV 1 -TK and ganciclovir (Immonen et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…However, in this trial the maximum tolerated dose was not reached. All patients showed tumour progression with a median time of 46 days and a median survival time of 6.2 months (Chiocca et al, 2004). One patient with anaplastic astrocytoma had stable disease and two patients who underwent a second resection had lymphocytic and plasmacytoid cell infiltration at the site of injection.…”
Section: Clinical Efficacy Of Adenovirus Mediated Gene Therapy In Glimentioning
confidence: 99%